Doing Outcomes‐Based Collaborative Teaching and Learning in Asia. (June 2015) - van Schalkwyk, Gertina J.
Abstract : This chapter focuses on applying the concepts of outcomes‐based collaborative teaching and learning in an Asian context and with students coming from a Confucian heritage culture and explores examples of how to implement effective collaborative teaching and learning in an Asian higher education setting.